Tinjauan Yuridis Pelanggaran Pemasangan Reklame Sesuai Peraturan Bupati Nomor 308/2023 Tentang Izin Penyelenggaraan Reklame (Studi Kasus Kabupaten Karawang) - Suryadi, Ismutiah; Asyhadi, Farhan; Abas, Muhamad (Wajah Hukum, 2025)
Billboards are promotional media designed to introduce or market goods, services, or individuals to the wider public. In Karawang Regency, the number of billboard installations increases annually in line with regional development, yet this growth is not accompanied by adequate supervision and law enforcement. Irregularities in billboard placement potentially disrupt urban aesthetics and violate existing regulations. The Karawang Regency Government regulates this matter through Regent Regulation Number 308 of 2023 as an implementation of Regional Regulation Number 3 of 2019 on Billboard Licensing. This study aims to identify the causes of weak law enforcement and the obstacles faced in billboard supervision. The research applies a socio-legal approach by examining the normative provisions in Regent Regulation Number 308 of 2023 and analyzing their implementation in practice. The findings indicate a lack of inter-agency coordination and limited socialization to the public and business actors. Therefore, strengthening inter-agency synergy, budget allocation, and legal education for the community is required to achieve orderly and compliant billboard management.